Determinants of smoking and smoking cessation among health professionals in Serbia: A cross-sectional study - Krstev Srmena; Marinković Jelena; Simić Snežana; Jovićević Ana; Marković-Denić Ljiljana (Vojnosanitetski Pregled)
Background/Aim. Bearing in mind a high smoking prevalence in Serbia (34% in adult population; men 38%, women 30%) and leading role of health professionals in intervention and prevention, a cross-sectional study was performed smong the representative sample of health professionals in Serbia. The aim of the study was to identify predictors of smoking and smoking cessation prior to the total smoking ban in November 2010. Methods. In this nationwide study, 3,084 physicians and nurses from 4 types of institutions and four geographical regions were selected and 2,282 included (response rate 74.0%). Data were collected using a self-administered structured questionnaire. Standard statistical methods were used to calculate prevalence rates, and multivariate logistic regressions to evaluate independent predictors of smoking pattern. Risks were expressed as odds ratios (OR) which represent approximation of relative risks of exposed persons with 95% confidence intervals (95% CI). Results. We found a high smoking prevalence of 38.0%, the same for women and men (37.8% and 37.6%, respectively; p = 0.138), higher among nurses (41.7%) than physicians (29.1%) (p = 0.000), as well as among those employed in general hospitals (42.6%) and institutes of public health (43.8%) (p = 0.000). Significantly increased risk of being an ever or current smoker was noticed for nurses (OR = 1.75, 95% CI 1.42-2.14; and OR = 1.91, 95% CI 1.52-2.40, respectively), those employed in general hospitals (OR = 1.37, 95% CI 1.09-1.73 and OR = 1.40, 95% CI 1.09-1.79, respectively), and with worse self-estimated health (OR = 1.15, 95% CI 1.02-1.30; and OR = 1.17, 95% CI 1.02-1.34, respectively). Intentions to quit smoking or to reduce the number of cigarettes were more frequent in women (OR = 1.51, 95% CI 1.01-2.27) and participants who worse evaluated their health (OR = 1.74, 95% CI 1.39- 2.18). Conclusion. High smoking prevalence in health professionals could be a barrier for the full implementation of smoking ban in health institutions in Serbia. Smoking cessation programs at workplaces, formal education in smoking cessation techniques, and better Law enforcement by health administrations should be implemented.